Vitamin D levels in IBD: a randomised trial of weight-based versus fixed dose vitamin D supplementation. (2nd June 2020) - Kojecky, Vladimir; Matous, Jan; Kianicka, Bohuslav; Dite, Petr; Zadorova, Zdena; Kubovy, Jan; Hlostova, Martina; Uher, Michal
Abstract: Objectives: Body weight is one of the factors affecting blood levels of 25-hydroxyvitamin D (25OHD). The aim of this study was to establish whether a vitamin D (vitD) weight-based dosing is more appropriate to a fixed daily dose in patients with inflammatory bowel disease (IBD). Materials/methods: This was an open label randomised trial. Patients with IBD were assigned to receive oral cholecalciferol at a dose of 28 IU/kg (IU/kg) or 2000 IU per day (IU/day) for 12 weeks during winter months. 25OHD plasma levels and other biochemical parameters were measured at baseline and after supplementation period. The primary outcome measure was 25OHD level after a follow-up period. Results: A total of 173 patients were analysed. The mean BMI was 25.5 ± 5.1 and initial mean 25OHD level was 62.7 ± 25.5 nmol/l. A similar increase (9.7 ± 26.9 vs 9.8 ± 26.7 nmol/l) in 25OHD levels occurred both in IU/kg and IU/day group. The proportion of subjects with normal and sub-normal levels following the substitution was comparable irrespective of body weight. The change in 25OHD level correlated positively only with the dose of vitD ( p  < .001) and negatively with the baseline 25OHD level ( p  < .001). A sustained 25OHD level of 75 nmol/l corresponds with a calculated daily vitD dose of 2034 IU. Conclusions: Weight-based dosing of vitamin D is not superior to a fixed dose in order to maintain stable 25OHD levels in IBD patients. Cholecalciferol dose of 2, 000 IU/day is safe and sufficient during winter period.